2016
DOI: 10.1016/j.actbio.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based hierarchical scaffolds for myoblast differentiation: Synergy between nano-functionalization and alignment

Abstract: Due to limited regenerative potential of skeletal muscle, strategies stimulating regeneration of functional muscles are important. These strategies are aimed at promoting differentiation of progenitor cells (myoblasts) into multinucleated myotubes, a key initial step in functional muscle regeneration. Recent tissue engineering approaches utilize various scaffolds ranging from decellularized matrices to aligned biomaterial scaffolds. Although, majority of them have focused on nano- or microscale organization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…In vitro models indicate that muscle progenitor cells utilize alignment cues during myogenesis. 39,40 Similar alignment-sensitive responses have been reported for other cells, including cardiac muscle and tendons. 41,42 Yet, while the many in vitro alignment studies support the motivation of aligned regenerative scaffolds, we recognize that in vivo evidence indicating that scaffold alignment is critical to muscle implant success does not yet exist.…”
Section: Decellularized Skeletal Muscle With Minced Muscle Autograftssupporting
confidence: 51%
“…In vitro models indicate that muscle progenitor cells utilize alignment cues during myogenesis. 39,40 Similar alignment-sensitive responses have been reported for other cells, including cardiac muscle and tendons. 41,42 Yet, while the many in vitro alignment studies support the motivation of aligned regenerative scaffolds, we recognize that in vivo evidence indicating that scaffold alignment is critical to muscle implant success does not yet exist.…”
Section: Decellularized Skeletal Muscle With Minced Muscle Autograftssupporting
confidence: 51%
“…Presence of graphene sheets on the surface (Figure d) may enhance the surface nanoroughness of the nanocomposite fibrous hydrogel films, leading to change in contact angle as well as cell adhesion and spreading. These properties along with fiber alignment at multiple length‐scale could provide contact guidance for the myoblasts to differentiate into myotubes and further, into functional muscle bundles (Patel, Mukundan et al, ). In our previous study, graphene–PCL electrospun scaffolds were shown to stimulate myoblast differentiation, however, these electrospun scaffolds lack multiscale hierarchy and aligned unidirectional fibers (Patel, Xue et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Surface characterization of fractured hydrogel films was carried out using SEM (Jeol 9335 Field Emission SEM; JEOL, Peabody, MA; Patel, Mukundan et al, ). Fractured hydrogel films were air dried after mechanical testing before SEM imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual fibers range from 5 to 100 um in diameter, and can be as long as several centimeters [50]. In-vitro models indicate that muscle progenitor cells utilize alignment cues during myogenesis [51, 52]. Similar alignment-sensitive responses have been reported for other cells, including cardiac muscle and tendons [53, 54].…”
Section: Discussionmentioning
confidence: 96%